STUDI PENERIMAAN KONSUMEN TERHADAP ABON NILA (Oreochromis niloticus) DENGAN PENAMBAHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Alik, Agustinus Tato’; Sukmiwati, Mery; Sari, Ira (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
This research was carried out to evaluate consumer acceptance of tilapia abon fortified with white oyster mushroom. Tilapia weighing 400-600 g each was taken from a fish market in Pekanbaru. Four types of fish abons were prepared from the fish meat which was fortified with white oyster mushroom 0%, 25%, 50%, and 75% of the fish weight. The fish abons were eval-uated for consumer acceptance by 80 panelist. The results indicated that the fish abons fortified with 25% white oyster mushroom was the most acceptable by consumer. Moisture, protein, fat, and crude fiber of the fish abon was: 5.83%, 33.79%, 29.03%, and 1.49% respectively.